2013
DOI: 10.1111/jcpe.12105
|View full text |Cite
|
Sign up to set email alerts
|

Gingival labial recessions in orthodontically treated and untreated individuals: a case – control study

Abstract: Within the limits of the present research design, orthodontic treatment and/or the retention phase may be risk factors for the development of labial gingival recessions. In orthodontically treated subjects, mandibular incisors seem to be the most vulnerable to the development of gingival recessions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
2
22

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(135 citation statements)
references
References 24 publications
3
108
2
22
Order By: Relevance
“…Only one of the studies reported error. 35 On the other hand, the statistical analysis was appropriate in all the studies; however, only one 36 reported having carried out combined analysis of subgroups. Confounders were not considered in any of the studies and the p value was described by all, but only one 36 established confidence intervals.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Only one of the studies reported error. 35 On the other hand, the statistical analysis was appropriate in all the studies; however, only one 36 reported having carried out combined analysis of subgroups. Confounders were not considered in any of the studies and the p value was described by all, but only one 36 established confidence intervals.…”
Section: Discussionmentioning
confidence: 99%
“…El estudio de Pandis 34 encontró que existe una alta prevalencia de recesiones gingivales en el grupo que utilizó retenedores a largo plazo. Un resultado similar se encontró en el estudio de Renkema,36 en donde se mostró que existe una relación entre el tratamiento de ortodoncia y/o la fase de retención con las recesiones gingivales a través del tiempo. Encontraron que el núme-ro promedio de las recesiones de los casos tratados se estima en un 142% superior a la de los controles, lo que demuestra que existe una asociación entre los pacientes con retenedores fijos y las recesiones gingivales, siendo los incisivos inferiores los dientes más vulnerables.…”
Section: Recesiones Gingivalesunclassified
See 3 more Smart Citations